Selected tumor markers in the diagnostics of prostate cancer - Darewicz, Barbara; Chabielska, Ewa; Chlabicz, Marcin; Dariusz Szajda, Sławomir; Werel, Tadeusz; Skrzydlewski, Zdzisław (Contemporary Oncology/Współczesna Onkologia, 2003)
The assessment of tumor markers in oncological diagnostics facilitate early detection and clinical staging as well as monitoring of treatment of neoplasmatic diseases. The aim of the study was to evaluate the usefulness of psa, cathepsin d and cancer procoagulant (CP) in the detection of prostate cancer. Serum PSA concentration and the activity of cathepsin D and CP were evaluated in 12 patients with prostate cancer and in 12 healthy men. PSA concentration was assessed using Axsym analyzer manufactured by Abbott and its value was expressed in ng/ml. The activity of cathepsin D was determined by Folin-Ciocalteau method in cupric modification and measured as the amount of released tyrosine in nM Tyr/ml/4h. The activity of CP was determined using the coagulative method according to Gordon and Benson, and was expressed as coagulation time in seconds (s). Serum PSA concentration and the activity of CP in patients with prostate cancer are over four times higher than the upper limit of normal PSA and than the mean serum activity of CP in healthy men (p<0.001). The serum activity of cathepsin D in patients with prostate cancer is close to normal value. The assessments of PSA concentrations and the activity of CP are of great diagnostic value.